Antiviral activity of chloroquine against Dengue virus type 2 replication in Aotus Monkeys - Farias, Kleber Juvenal Silva (Mary Ann Liebert, 2020)
Dengue virus (DENV) of the Flaviviridae family is a single positive-stranded RNA virus that is transmitted by Aedes aegypti and Aedes albopictus mosquitoes. The objective of this study was to investigate the use of chloroquine (CLQ) as an antiviral drug against dengue virus in monkeys. To analyze the action of the drug in vivo, nonhuman primates groups (Aotus azarai infulatus) were inoculated with a subcutaneous injection of a virulent strain of DENV-2, treated and untreated CLQ. Blood hematological, viremia, and serum biochemical values were obtained from 16 DENV-2-inoculated, treated and untreated; four received only CLQ and one mock-infected Aotus monkeys. Monkey serum samples (day 0?10 post-inoculation) were assayed by reverse transcription polymerase chain reaction and Cytometric Bead Array for determination of viremia and inflammatory cytokines, respectively. Additionally, body temperature and activity levels were determined. In the present work, CLQ was effective on replication of DENV-2 in Aotus monkeys; a time viremia reduction was observed compared with the controls. The concentration of tumor necrosis factor alpha and interferon gamma in the serum of the animals had a statistically significant reduction in the groups treated with CLQ after infection compared with the controls. A significant decrease in systemic levels of the liver enzyme aspartate aminotransferase (AST) was also observed in the animals treated with CLQ after infection compared with the controls. These results suggest that CLQ interferes in DENV-2 replication in Aotus monkeys.